ANALISIS KEMAMPUAN PEMAHAMAN DAN KEYAKINAN MATEMATIK PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN STRATEGI KONFLIK KOGNITIF - Sujiarto, Heru; Lestari, Puji Budi (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
The skill of mathematical understanding and student’s belief to mathematic are an important elements one student should have, to help students to solve mathematic problems, along with daily problems. One of the ways to analysis this is through a learning process where a situation, fact, and condition that polarize student’s cognitive structure are involved. In such situation, conflict between student’s knowledge and designed situation happened. The main problem of this research is about how the analysis understanding skill and student’s mathematical belief, are reviewed based on learning method (cognitive conflict strategy and conventional), and school rank (high and middle). This research is an experiment with pretest-posttest control group design. Cognitive conflict strategy is given to the experiment group, while conventional learning is given to control group. This research is involving 140 seventh grade students in Bandung City that represent schools in high and middle rank. The instruments of this research is Mathematical Understanding Skill test and Mathematical Belief scale. Data analysis used in the hipotesist test is t-test, two way Anova, and Scheffe test. The summary of this research is, In general, student’s mathematical understanding skill and student’s mathematical belief that is given the cognitive conflict strategy and school rank (high and middle) is significantly different than student that is given the conventional learning.